Pelatihan dan Pendampingan Pembuatan Alat Permainan Edukatif Pada IKM Bermain Bagi Guru TK di Kabupaten Lahat - Rukiyah, Rukiyah; Suningsih, Taruni; Rantina, Mahyumi; Akbari, Akbari; Khotimah, Khusnul; Rahmawati, Rahmawati; Fuspita, Della (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: The implementation of the Merdeka Curriculum for Play has not been implemented properly by Kindergarten Teachers in Lahat Regency, because they have not been able to create and optimize Educational Game Tools that are in accordance with implementation of Merdeka Curriculum for Play at the Early Childhood Education level. Also, as a form of collaboration between the Lahat Regency Government and Sriwijaya University in building superior Human Resources, especially Kindergarten Teachers, to be more qualified, competitive, and have character in improving competence as Kindergarten Teachers. The aim of this activity is to provide understanding in the form of training and mentoring in making educational game tools on the implementation of the Merdeka Curriculum for Play in Kindergarten Teachers at Lahat Regency. Method: This activity involved 20 Kindergarten Teachers in Lahat Regency, South Sumatra Province. The stages of this Community Service Activities are divided into 3, namely: 1) Planning; 2) Implementation; and 3) Evaluation. Result: Increase in teacher knowledge after participating in this activity with pre-test and post-test results of 32,25 points and an N-gain value of 77,24% in the Effective category. There is an increase in the ability of Kindergarten Teachers in Lahat Regency to make educational game tools on the implementation of the Merdeka Curriculum for Play. Conclusion: That activities were carried out effectively, received a positive response, and increased new knowledge for Kindergarten Teachers in Lahat Regency.